How parts make up wholes - Findlay, Scott D.; Thagard, Paul (Frontiers in Physiology, 2012)
We propose a schema that characterizes how parts constitute wholes at diverse levels of organization, ranging from the atomic to the biological to the social. This schema of tags, organizers, attachers, and communicators provides a unified understanding of the structure, function, and dynamics of organization in physics, biology, and the cognitive and social sciences. We use this schema to identify and describe structures and processes at many levels of organization, and discuss its relevance for understanding the nature of constitution and emergence, especially the relation between individual humans and the social groups they constitute.